2018
DOI: 10.5332/hatsuhatsu.2018.78_43
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of physical activity, depression, and sense of coherence in early adolescents

Abstract: A survey was conducted to assess physical activity, depression, and sense of coherence among early adolescents. This study used a cross-sectional sample of 12,086 students(G5-G9)from 28 public elementary schools and 22 public junior-high-schools in Japan. A total of 9,424 students(G5-G8)were surveyed from December 2013 to December 2015 using the International Physical Activity Questionnaire [資 料] 発育発達研究 第 78 号 (IPAQ) -short form to measure physical activity (PA), the Depression Self-Rating Scale for Children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These signs were similarly represented by the items in the PPH questionnaire used in this study. Furthermore, previous studies on the PPH and physical activity of schoolchildren have reported that girls have a stronger tendency toward anxiety and depression than boys (Kawakatsu et al, 2018;Wiles et al, 2008). Our findings may reflect a decline in psychosocial health with age, which is more obvious in girls aged six to nine years given their more advanced growth relative to boys of the same age.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These signs were similarly represented by the items in the PPH questionnaire used in this study. Furthermore, previous studies on the PPH and physical activity of schoolchildren have reported that girls have a stronger tendency toward anxiety and depression than boys (Kawakatsu et al, 2018;Wiles et al, 2008). Our findings may reflect a decline in psychosocial health with age, which is more obvious in girls aged six to nine years given their more advanced growth relative to boys of the same age.…”
Section: Discussionmentioning
confidence: 96%
“…Relevant items were retrieved from the literature, including reports in “The National Network of Physical and Mental Health in Japanese Children” (2016). These items are widely used to measure children’s PPH in the school setting in Japan, and they include the following: ‘Do you have abdominal pain?’ (Chen et al, 2004; Ministry of Education, Culture, Sports, Science and Technology [MEXT], 2011; Kamikawa, 2011; Kawakatsu et al, 2018; Wiles et al, 2008), ‘Do you feel sleepy in the daytime?’ (Kamikawa, 2011; Kawakatsu et al, 2018; Shikano and Noi, 2014), ‘Do you feel dull when you get up in the morning?’ (Kamikawa, 2011; Shikano and Noi, 2014), ‘Do you sleep well at night?’ (Carskadon et al, 1993; Kamikawa, 2011; Meijer et al, 2000), ‘Do you yawn in the morning?’ (Kamikawa, 2011; Shikano and Noi, 2014), ‘Do you feel dizzy?’ (MEXT, 2011; Kamikawa, 2011; Shikano and Noi, 2014; Editorial Board of the Annual Report of Physical and Mental Health among the Children, 2015), ‘Do you feel sick?’ (MEXT, 2011; Kamikawa, 2011; Shikano and Noi, 2014), ‘Do you feel unmotivated?’ (Kamikawa, 2011; Shikano and Noi, 2014), and ‘Do you feel irritated?’ (Kamikawa, 2011; Shikano and Noi, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations